A Rhetorical Study of Persuasion in Selected TED Talks - Mohammed, Serin Majeed; Mayuuf, Hussain Hameed (Journal of Posthumanism, 2025)
This study employs a rhetorical approach to analyse the persuasiveness of TED Talks. The researcher intends to examine the use of persuasive strategies and the rhetorical strategies employed by TED Talks presenters in their speeches. The researcher tries to uncover the effectiveness of using such rhetorical aspects and how speakers effectively engage and persuade their audience. To achieve the aims of the study and to answer the research questions, it has been hypothesised that TED Talk presenters employ different persuasive and rhetorical strategies via which they intend to persuade their audience and make them believe certain allegations and justifications. Two presentations have been selected as samples of the current study. The selected data have been analysed qualitatively according to Lucas’ (2009) theory of persuasive strategies and Leech’s (1969) theory of rhetorical strategies. After analysing the selected data, it has been concluded that TED Talks presenters used some persuasive strategies like pathos, ethos and logos; this conclusion proves the first hypothesis of the study. It has also been concluded that they employ some rhetorical strategies like metaphor, metonymy, hyperbole, simile and personification; this conclusion confirms the second hypothesis of the study. By utilising such persuasive and rhetorical strategies, the presenters try to convince their audience of particular claims and make their audience believe their justifications of such claims.